Radiation exposure during neurointerventional procedures in modern angiographic systems: A single center experience - Lukić, Snežana; Rasulić, Lukas; Kovačević, Vojin; Vitošević, Filip; Savić, Andrija; Mijailović, Milan (Vojnosanitetski pregled, 2021)
Background/Aim. Interventional neuroradiology procedures expose patients to ionizing radiation. The aim of this study was to assess doses received by patients during interventional neuroradiology procedures and to establish dose range with an estimate of risk from adverse consequences of irradiation. Methods. Our study describes series of patients submitted to diagnostic and/or therapeutic procedures at the Department of Interventional Neuroradiology, Clinical Center Kragujevac, Serbia, from December 1, 2014 to December 1, 2016. The following variables were considered for this study: kerma-area product, air kerma and fluoroscopy exposure time; peak skin dose and effective dose calculated from the kerma-area product. Results. Median kerma-area product was 87.802 Gy∙cm2, 78.567 Gy∙cm2, 117.626 Gy∙cm2; effective dose was 12.731 mSv, 11.392 mSv, 17.056 mSv; peak skin dose was 0.456 Gy, 0.409 Gy, 0.612 Gy, and estimated brain dose was 254.62 mGy, 227.84 mGy, 341.12 mGy, for diagnostic, therapeutic and combined procedures, respectively. Conclusion. Interventional neuroradiology procedures show significant variability in radiation dose, due to patient constitution, radiologist expertise and equipment factors. Knowing the doses can have a great benefit for patients and medical and paramedical stff in terms of prevention of possible deterministic and stochastic effects of the radiation.
Keywords: dose-response relationship, radiation; neuroradiography; radiation dosage; radiation protection